2021
DOI: 10.1002/alz.058692
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of the β amyloid peptide with bacteria in postmortem brain tissue of patients with familial Alzheimer's disease

Abstract: Background β‐amyloid (βA) is a highly conserved peptide throughout the evolution of species that has been proposed as a participant in vital functions. This peptide has been related to the onset and progression of Alzheimer’s disease (AD). Additionally, recent scientific reports have demonstrated in vitro activity against bacteria, fungi and virus. The aim of this study is to describe the colocalization between βA and bacteria in postmortem brain tissue of patients with familial AD. Method Initially, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, β-amyloid deposition in the hippocampus was measured with immunohistochemical staining. β-amyloid plaques produced by amyloid deposition in the brain are characteristic pathological changes of Alzheimer’s disease ( 38 ). Previous study has shown that fermented milk of Lactobacillus helveticus IDCC3801 reduced β-amyloid and improved memory deficit ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, β-amyloid deposition in the hippocampus was measured with immunohistochemical staining. β-amyloid plaques produced by amyloid deposition in the brain are characteristic pathological changes of Alzheimer’s disease ( 38 ). Previous study has shown that fermented milk of Lactobacillus helveticus IDCC3801 reduced β-amyloid and improved memory deficit ( 39 ).…”
Section: Discussionmentioning
confidence: 99%